2017
DOI: 10.1093/annonc/mdx411
|View full text |Cite
|
Sign up to set email alerts
|

DPYD genotype-guided dose individualization to improve patient safety of fluoropyrimidine therapy: call for a drug label update

Abstract: The fluoropyrimidine anticancer drugs, especially 5-fluorouracil (5-FU) and capecitabine, are frequently prescribed for several types of cancer, including breast, colorectal, head and neck and gastric cancer. In the current drug labels of 5-FU and capecitabine in the European Union and the United States, no adaptive dosing strategies are incorporated for polymorphic metabolism of 5-FU. Although treatment with fluoropyrimidines is generally well tolerated, a major clinical limitation is that a proportion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 59 publications
1
73
0
Order By: Relevance
“…(Toffoli et al, 2015;Deenen et al, 2016) However, the major limitation of DPYD*2A of being used as a predictive marker for toxicity is its lower minor allele frequency varying from 0.1 % to 1% in different ethnic groups. (Henricks et al, 2017) A recent study states that only a 50 % patients with DPYD*2A carriers actually develop toxicity with 5-FU treatment and reported that novel DPYD variants, DPYD*9 and DPYD*6 carry 2 fold higher risk for toxicities with 5 -FU treatment when compared to DPYD*2A polymorphism alone (Gentile et al, 2016). This emphasizes the search for novel genetic toxicity predictive markers for capecitabine treatment.…”
Section: Influence Of Dpyd*9a Dpyd*6 and Gstp1 Ile105val Genetic Polmentioning
confidence: 99%
“…(Toffoli et al, 2015;Deenen et al, 2016) However, the major limitation of DPYD*2A of being used as a predictive marker for toxicity is its lower minor allele frequency varying from 0.1 % to 1% in different ethnic groups. (Henricks et al, 2017) A recent study states that only a 50 % patients with DPYD*2A carriers actually develop toxicity with 5-FU treatment and reported that novel DPYD variants, DPYD*9 and DPYD*6 carry 2 fold higher risk for toxicities with 5 -FU treatment when compared to DPYD*2A polymorphism alone (Gentile et al, 2016). This emphasizes the search for novel genetic toxicity predictive markers for capecitabine treatment.…”
Section: Influence Of Dpyd*9a Dpyd*6 and Gstp1 Ile105val Genetic Polmentioning
confidence: 99%
“…Current evidence supports upfront DPYD screening for four DPYD variants ( DPYD * 2A, c.2846A>T, c.1679T>G, and c.1236G>A), followed by genotype-guided dosing, based on dosing recommendations by the CPIC. This clinical utility has been confirmed by two recent large-scale studies ( 20 , 21 ) and drug label update has been called ( 22 ).…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, the rs17116806 has been also associated to an increased susceptibility to colorectal carcinogenesis, demonstrating that the same polymorphism can act on tumorigenesis in different tissues. International regulatory agencies, such as the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA), strongly recommend the monitoring of polymorphisms on the DPYD gene for evaluation of therapeutic response in fluoropyrimidine-based treatment [29] [30]. Nevertheless, few investigations have studied genetic variations in the DPYD gene regarding cancer susceptibility, thus, the variety of clinical manifestations resulting by mutations in DPYD is still not well understood [31].…”
Section: Discussionmentioning
confidence: 99%